Severe creatine kinase increase during quetiapine and mirtazapine treatment - RABUŞ, ŞULE (SPRINGER, 2006)
In the literature, there have been several publications reporting creatine kinase (CK) increases associated with the use of atypical antipsychotic drugs. In this letter, I would like to present a case in which there was a massive increase in serum CK levels together with relatively modest increases in serum CK myoglobin-band (CK-MB), lactate dehydrogenase (LDH), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels during quetiapine and mirtazapine treatment, without the presence of neuroleptic malignant syndrome (NMS).
Keywords: ANTIPSYCHOTIC-DRUGS; OLANZAPINE; ELEVATIONS; CLOZAPINE